Stereotypical representations of the oher in nineteenth-century satirical journals: John Bull versus Zé Povinho - Paisana, Joanne (2012)
The use of national stereotypes will be examined in this chapter both in a contemporary and historical context. The timelessness of John Bull and Zé Povinho is confirmed with two examples. The first is the Birmingham Mail’s on-line article by Jon Griffin entitled “John Bull to stand as Mayor in Birmingham”, (December 8, 2010), which recounts how retired policeman and election candidate Ray Egan was running for mayoral office dressed as John Bull, a strategy designed to enhance his patriotic appeal. The second example is from the Público newspaper’s front page leading article for October 10, 2010. The headline reads – “PSD accuses PS of budget ‘blackmail’ but is simultaneously willing to negotiate”. The current economic crisis is succinctly correlated with that of two centuries earlier through the reproduction of an illustration showing a prostrate Zé Povinho literally ‘saddled’ with a plethora of useless politicians who, although rotating in office, have produced similar disastrous results to those attained by the recent political incumbents of São Bento. Using this type of stereotypical 'short-hand' can be useful but the risks endemic in any stereotype should not be forgotten, especially the inability to reflect nuance because of standardization.John Bull and Zé Povinho were also used around 1890 in a propaganda war of words and images concerning colonial aspirations in Africa. This exchange will be briefly examined, and a few of the many illustrations analysed, showing how these two supposed allies were capable of portraying each other in a negative way.